Обратный отсчет - Пучков Лев Николаевич (К.Т.О. Контртеррористическая операция, 2014)
Экземпляры: аб. ЦБ (2017.14.12) / Инвентарный номер: 3642 / Цена: / Сис.шифр: 84 (2Рос=Рус)6-44 / Авт.знак: П 90 / ББК: 84 (2Рос=Рус)6-44